VR/AR in Customer Experience: A Bibliometric Review - Loso Judijanto; Tati Handayani (Westscience Press, 2026)
The current study offers a bibliometric analysis of academic research on VR/AR in customer experience, whose objectives include exploring the intellectual structure, thematic trends, and global patterns of cooperation within the research area. Data for the analysis were collected from a scientific database and analyzed via bibliometric methods such as co-word analysis, co-authorship mapping, density visualization, and citation analysis in VOSviewer software. The findings show that VR and AR represent the main research constructs which have close relationships with user experience, e-commerce, digital marketing, and human-computer interaction. Thematic trend analysis shows a transformation from basic research on the usability and immersivity of the interface towards more applied studies focused on e-commerce, tourism, and metaverse customer experiences. Citation analysis highlights a number of highly impactful publications that have contributed significantly to the theoretical and methodological development of the field, in particular, to experiential marketing and technology-driven customer experience. Network analysis also highlights the global, although uneven, nature of collaboration networks and certain hub countries in international cooperation.